DESCRIPTION OF LIFE EVENTS IN MUSICAL DRAMAS (on the example of the musical drama "Vijdon") (ART AND CULTURE BULLETIN, 2025)
In this article, the specific features of the art of Karakalpak musical drama, in particular,the artistic expression of life events in it, are analyzed using the example of the musical drama “Vijdon”
Keywords: theatre; musical drama; life story; method of expression; plot